Replacement of dietary groundnut-cake by soybean-meal supplemented with dlmethionine on the performance of layer chickens - NAULIA, UMA; SINGH, K S (The Indian Journal of Animal Sciences, 2014)
Single comb White Leghorn hens (90) of 24 week-old (average B Wt. 1200Â±20g) were divided in a completely randomised design for S treatments with 3 replicates of6 bird each. The birds were fed on diets containing groundnul. cake (GNC) replaced by soybcanÂ·meal (SBM) supplemented with DL-mcthionine. The GNC was replaced by SBM (on nitrogen basis) at 0, 25. 50. 75 and 100% levels. The percent hen-day egg production at 75% replacement level was significantly higher (P<0.05) than that on 0.25 and 100% levels without affecting the feed consumption. Although. the dry matter. organic matter digestibilities and the calcium retention were significantly higher (P<0.05) at 75%Â replacement level but did not differ to 50 and 100% replacement levels. However the teed conversion ratio (g feed/egg) at 50% replacement level was significantly higher. The cost of egg production was significantly lowest (Rs 1.02/egg) of 50% replacement diet than that of sole’source of GNC and SBM based (0 and 100% replacement) diets, respectively. The egg, quality traits: weight. specific graviry;’shape index, shell thickness, yolk and albumen index of eggs remained unchanged due to the treatments. Thus,the 50% replacement ofGNC by SBM supplemented with DL-methionine in the layer chicken diets improved egg produdion, feed coil version ratio, nutrient digestibility and retention, and also lowered the cost of egg production.